Viability of introduced plants of the genus Lonicera L. in the Kola Subarctic - Goncharova Oxana Alexandrovna (Hortus Botanicus, 2023)
The article contains a list of introduced specimens of the genus Lonicera L. in the collection fund of the Polar-Alpine Botanical Garden-Institute. The PABSI collection includes 50 specimens of introduced plants of the genus Lonicera, belonging to 16 species, 8 intraspecific taxa and 2 hybrids. The age of collection honeysuckles is from 8 to 82 years. Most of the samples of honeysuckle surveyed are viable and are distinguished by high decorative qualities, winter-hardy and retain their vital form. The most viable, promising for introduction and have high decorative qualities are L. involucratа and L. caerulea. The study is one of the stages of a comprehensive description of plants states when introduced into the conditions of the Far North.